Two-period resource duopoly with endogenous intertemporal capacity constraints - Istemi Berk (Institute of Energy Economics at the University of Cologne (EWI), 2014)
This paper analyzes the strategic firm behavior within the context of a two-period resource duopoly model in which firms face endogenous intertemporal capacity constraints. Firms are allowed to invest in capacity in between two periods in order to increase their initial endowment of exhaustible resource stocks. Using this setup, we find that the equilibrium price weakly decreases over time. Moreover, asymmetric distribution of initial resource stocks leads to a significant change in equilibrium outcome, provided that firms do not have the same cost structure in capacity additions. It is also verified that if only one company is capable of investment in capacity, the market moves to a more concentrated structure in the second period.
Keywords: D43; L13; Q32; Q4; 330; Dynamic Duopoly; Cournot Competition; Endogenous Intertemporal Capacity Constraints; Subgame Perfect Nash Equilibrium